The Role of Organoleptic Tests in Introducing Innovations on The Example of Solutions from The Light Industry Sector - Paweł TUREK; Elżbieta BIELAK (Communications of International Proceedings, 2021)
The article presents the results of the sensory research on subjective impressions related to scents of the following essential oils: cinnamon, eucalyptus, manuka, oregano and thyme as well as the desirability of their scents. These substances, due to their antiseptic effects, were proposed in the previous research to enriching leathers, dedicated to inside elements of shoes, in order to give them resistance and activity against microorganisms harmful in tanning industry and with potential pathogenic effects to humans. The group of respondents (N=148) consisted of 94 women (63.5%) and 54 men (36.5%). The mean age of the participants was 24.2 with a standard deviation of 8.6 (19-52). The organoleptic tests performed in a controlled area (laboratories of the sensory analysis of the Cracow University of Health Promotion), in accordance with the international standard ISO 11136:2014 showed semantic differences between the examined scent profiles as well as significant differences between average evaluations in the general desirability of oil scents. The highest desirability was observed for cinnamon and eucalyptus oils, in the case of which no statistically significant differences in consumer evaluations were revealed, as opposed to the other oils. The previously conducted microbiological research showed that the antimicrobial effect on a proper level can be obtained by treating leather with oregano oil, and, subsequently, with cinnamon and thyme oils. When comparing the results of the sensory and microbiological experiments, the most optimal oil with the scent preferred by consumers and ensuring a good and long-lasting antimicrobial effect of leathers was cinnamon oil.
Keywords: Scent; Sensory analysis; Essential oils; Lining leather; Consumer.